1987
DOI: 10.2118/16243-pa
|View full text |Cite
|
Sign up to set email alerts
|

Settling Velocity of Variously Shaped Particles in Drilling and Fracturing Fluids

Abstract: Summary The settling velocities of a variety of shaped particles to simulate drilled cuttings were measured in both Newtonian and non-Newtonian fluids. The results showed that the particle drag coefficient is a function of the particle Reynolds number and, in the case of power-law-model fluids, of the flow behavior index. A new generalized model has been developed for predicting the setting velocities of particles of various shapes in both Newtonian and power-law fluids over a range of flow r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…Torrest [26] claimed that Stokes's law is capable of describing the settling of gravel chips in viscous non-Newtonian hydroxyethyl cellulose polymer solutions. Peden and Luo [27] reported the settling velocity of cylindrical and disk-shaped particles in drilling and fracturing fluids. Reynolds and Jones [28] measured the drag forces on various types of particles in non-Newtonian fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Torrest [26] claimed that Stokes's law is capable of describing the settling of gravel chips in viscous non-Newtonian hydroxyethyl cellulose polymer solutions. Peden and Luo [27] reported the settling velocity of cylindrical and disk-shaped particles in drilling and fracturing fluids. Reynolds and Jones [28] measured the drag forces on various types of particles in non-Newtonian fluids.…”
Section: Introductionmentioning
confidence: 99%
“…It was also noted that the data could have been influenced by the confining walls but no wall correction was applied. Peden and Luo (1987) have also reported experimental data of spheres falling in aqueous solutions of CMC and HEC. The two constants in the relationship between drag coefficient and particle Reynolds number were reported to be functions of the power law flow behavior index but the dependence was found to be irregular.…”
Section: Review Of Previous Workmentioning
confidence: 97%
“…In his investigation, unfortunately Chhabra (1990) did not acknowledge and include the relevant work reported in the petroleum engineering literature, except the study of Peden and Luo (1987). Novotny (1977) studied particle transport using vertical fractures.…”
Section: Review Of Previous Workmentioning
confidence: 99%
“…The determination of this coefficient for Newtonian fluids has been a subject of numerous investigations in the past [86][87][88]. Several drag coefficient models for non-Newtonian fluids have also been proposed [89][90][91][92][93][94][95]. Chhabra [96] carried out a detailed comparison of the different correlations developed by the different authors for power law fluids and found out that correlations by Acharya et al [93] and Matijasic and Glasnovic [95] gave the best result followed by that of Darby [94].…”
Section: Drag Coefficient For Foammentioning
confidence: 99%